2021
DOI: 10.1002/ijgo.13958
|View full text |Cite
|
Sign up to set email alerts
|

Climate change, women’s health, and the role of obstetricians and gynecologists in leadership

Abstract: Climate change is one of the major global health threats to the world's population. It is brought on by global warming due in large part to increasing levels of greenhouse gases resulting from human activity, including burning fossil fuels (carbon dioxide), animal husbandry (methane from manure), industry emissions (ozone, nitrogen oxides, sulfur dioxide), vehicle/factory exhaust, and chlorofluorocarbon aerosols that trap extra heat in the earth's atmosphere. Resulting extremes of weather give rise to wildfire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 97 publications
(191 reference statements)
0
47
0
6
Order By: Relevance
“…Although our participants expressed some preoccupation with climate change (as reflected in moderate scores for the preoccupation subscale of CCPQ), it was not relevant to their reproductive intentions. The literature suggests that climate change’s effect on a person’s health is important because it is related to reproductive health as well [ 9 ]. Participants might have been aware of such a link and responded accordingly in our study; therefore, the findings indicated the predictive role of health-related climate concerns, but did not indicate the importance of a general preoccupation with climate change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our participants expressed some preoccupation with climate change (as reflected in moderate scores for the preoccupation subscale of CCPQ), it was not relevant to their reproductive intentions. The literature suggests that climate change’s effect on a person’s health is important because it is related to reproductive health as well [ 9 ]. Participants might have been aware of such a link and responded accordingly in our study; therefore, the findings indicated the predictive role of health-related climate concerns, but did not indicate the importance of a general preoccupation with climate change.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence of the effect of adverse environmental conditions on fertility as well as on reproductive plans was found in countries such as Mexico [ 5 ], Indonesia [ 6 ], Bangladesh [ 7 ], and Zambia [ 8 ]. Adverse environmental changes are also considered as imminent health risk factors to pregnant persons, their fetuses, and reproductive health in general [ 9 ] and also as a public mental health issue [ 10 ]. Another wave of discussion links climate change to overpopulation.…”
Section: Introductionmentioning
confidence: 99%
“…For me, this is the most important reason of all to minimise the use of CS or operating theatre usage where possible. Climate change disproportionately affects women and is the most critical long‐term determinant of planetary health 38 . For some reason the environmental effects of climate change are rarely mentioned by ideological critics, yet, of all of the purported reasons to avoid a CS, this to me is the most impactful (Fig.…”
Section: Caesarean Birth and Its Effects On The Health Systemmentioning
confidence: 99%
“…As reported by the World Health Organization (WHO) and The Lancet Countdown, climate change can have a great impact on human health. 1 Particularly vulnerable populations are pregnant women, children, foetuses, the elderly, and disadvantaged populations. In fact, epidemiologic evidence suggests the direct effect of climate change on fertility, perinatal outcomes, reproductive and mental health.…”
Section: Introductionmentioning
confidence: 99%
“…The current climate crisis constitutes an environmental emergency. As reported by the World Health Organization (WHO) and The Lancet Countdown, climate change can have a great impact on human health 1 . Particularly vulnerable populations are pregnant women, children, foetuses, the elderly, and disadvantaged populations.…”
Section: Introductionmentioning
confidence: 99%